Survey data from a survey about cybersecurity training and usability of security functions - Kävrestad, Joakim (University of Skövde, 2021)
This data set was acquired using a survey which intends to measure:
• Participants previous experience of cybersecurity training
• Participants perception of ideal cybersecurity training
• Participants perception of a specific cybersecurity training type called ContextBased MicroTraining
• What usability aspects the participants find most important for security features
Data was acquired from Sweden, UK and Italy to allow for comparative analysis. Demographic data was collected to allow for further analysis based on those. The files included in this data set are:
• Completesurvey: This document includes the full survey presented to the participants.
• Dataset: This file contains the variables and data for the different questions (available as .sav (SPSS and .csv)).
• Var_info: contains information about the variables in the dataset
• Overview: Contains frequency tables for the survey question (for the complete data set)
• Sweden, UK, and Italy: Contains frequency tables for the survey questions divided by national sample groups.

Se attahed description

Enkätdata från enkät om cybersäkerhetsträning och användbarhet av säkerhetsfunktioner. Data insamlad från svarande i Sverige, UK, och Italien.

Se bifogad beskrivning
Enkätdata från enkät om cybersäkerhetsträning och användbarhet av säkerhetsfunktioner
Keywords: education; utbildning; cybersecurity; cybersäkerhet; usability; användbarhet; Information society; Informationssamhället; Computer Sciences; Datavetenskap (datalogi); Information Systems; Systemvetenskap, informationssystem och informatik